Essential account planning : 5 keys for helping your sales team drive revenue - Donnolo, Mark (ATD Press, 2017)
Sales growth starts with planning Sales accounts are harder than ever to win, let alone keep. Globalization, cloud computing, and crowdsourcing create a marketplace where any account can be lured away by a hungry startup. And the face-time advantage? Forget it. Today's high-quality sale will likely involve six or more decision makers. That's why it's time to get strategic about how sales teams frame their approach. In Essential Account Planning, sales enablement expert Mark Donnolo blends his years of experience with expert interviews and stories to show you how planning can reliably drive revenue. His five-point framework will prepare you to address the arguments you're certain to hear against account planning, such as lack of commitment, ownership, and time. Each sales organization is unique, but most have similar challenges and succeed using common principles. And chances are, sales reps in your company already perform many of these account planning tasks, albeit on the fly or independent of others. This book's ready-to-use tools and templates will help you get everyone on the same page to deliver immediate results. In this book, you'll learn how to: Develop a consistent account plan structure. Create the habits and culture of an ongoing planning process. Navigate the politics that impede information sharing. Many salespeople believe that more selling creates more sales, but the salespeople who invest in account planning become the true sales leaders. Use Essential Account Planning to bring stability to your sales organization and start seeing the rewards of planning today!